Human Y chromosome microdeletion analysis by PCR multiplex protocols identifying only clinically relevant AZF microdeletions - Vogt, Peter H.; Bender, Ulrike (Spermatogenesis, 2013)
PCR multiplex assays are the method of choice for quickly revealing genomic microdeletions in the large repetitive genomic sequence blocks on the long arm of the human Y chromosome. They harbor the Azoospermia Factor (AZF) genes, which cause male infertility when functionally disrupted. These protein encoding Y genes are expressed exclusively or predominantly during male germ cell development, i.e., at different phases of human spermatogenesis. They are located in three distinct genomic sequence regions designated AZFa, AZFb, and AZFc, respectively. Complete deletion of an AZF region, also called “classical” AZF microdeletion, is always associated with male infertility and a distinct testicular pathology. Partial AZF deletions including single AZF Y genes can cause the same testicular pathology as the corresponding complete deletion (e.g., DDX3Y gene deletions in AZFa), or might not be associated with male infertility at all (e.g., some BPY2, CDY1, DAZ gene deletions in AZFc). We therefore propose that a PCR multiplex assay aimed to reduce only those AZF microdeletions causing a specific testicular pathology—thus relevant for clinical applications. It only includes Sequence Tagged Site (STS) deletion markers inside the exon structures of the Y genes known to be expressed in male germ cells and located in the three AZF regions. They were integrated in a robust standard protocol for four PCR multiplex mixtures which also include the basic principles of quality control according to the strict guidelines of the European Molecular Genetics Quality Network (EMQN: http://www.emqn.org). In case all Y genes of one AZF region are deleted the molecular extension of this AZF microdeletion is diagnosed to be yes or no comparable to that of the “classical” AZF microdeletion by an additional PCR multiplex assay analyzing the putative AZF breakpoint borderlines.